Peningkatan Kemampuan Kognitif (Konsep Bilangan) Anak Melalui Media Kartu Angka Matching - Elza Novrianti; Ela Pebriani; Lydia Margaretha (Early Childhood Research and Practice, 2026)
This study aims to enhance children's cognitive abilities—specifically regarding number concepts—through the use of matching number cards in early childhood education (PAUD). The study employs the Classroom Action Research (CAR) method, conducted over two cycles; each cycle comprises the stages of planning, action implementation, observation, and reflection. The research subjects consisted of 12 children from Group B (aged 5–6 years). Data collection was carried out through observation and documentation, while data analysis utilized quantitative descriptive analysis with percentages. The results indicate that the use of matching number cards can improve children's cognitive abilities in recognizing number concepts. This improvement is evident in the percentage results across each cycle. In Cycle I, Meeting 1, the children's cognitive ability score was 41.66% (categorized as "Starting to Develop" or MB), rising to 56.25% in Cycle I, Meeting 2 (categorized as "Developing as Expected" or BSH). Subsequently, the score increased to 70.83% in Cycle II, Meeting 1, and reached 83.33% in Cycle II, Meeting 2 (categorized as "Developing Very Well" or BSB). The improvement in cognitive ability was demonstrated by the children's proficiency in recognizing number symbols, counting objects, matching numbers to images, and correctly sequencing numbers. The use of matching number cards created an engaging, active, and enjoyable learning atmosphere, making it easier for children to grasp number concepts through "play-while-learning" activities. Thus, matching number cards have proven effective in enhancing the cognitive abilities of early childhood learners regarding number concepts.